Lysis of 'Escherichia coli' for the Recovery of Pentamerised Single-Domain Antibody Used for the Gender Specific Separation of Bovine Sperm - O'Reilly, Jordan (Université d'Ottawa / University of Ottawa, 2016)
Gender of animal offspring is of great interest to farmers where gender selection is achieved via the separation of male-bearing from female-bearing sperms prior to performing artificial insemination. A start-up company (Ab Biotech Inc.) has developed a technique for gender selection based on the production of an intracellular single-domain antibody (sdAb) using the bacterium Escherichia coli capable of sexing bovine sperm. The purpose of this research was to provide a recommendation to Ab Biotech Inc. for the lysis of E. coli. An efficient lysis technique was required in order to release the intracellular sdAb. In the dairy industry, sexing for female calves is preferred since male calves are not useful for the purpose of milk production. Multiple lysis techniques were tested in order to provide a feasible recommendation for Ab Biotech Inc. These techniques included high pressure homogenization, sonication, bead milling and enzymatic/chemical lysis using lysozymes and Triton X-100. Required lysis time, extent of lysis and potential operating costs were contributing factors for determining an optimal technique. The extent of lysis was determined by quantifying the total amount of released protein using SDS-PAGE densitometry. It was recommended to choose bead milling for potential process upscaling since a large amount of fractional lysis (0.70) was obtained over a short amount of lysis time (3 min) with an inexpensive ($9.50/kg) 0.3 mm mixture of glass beads.
Keywords: Cell Lysis Methods; E. coli; Single-Domain Antibody; Sperm Sexing